A SYSTEMATIC REVIEW PROTOCOL OF RECOVERY SOCIAL SUPPORT FOR WOMEN WITH DRUGS ADDICTION - Hidayati, Rizqi Wahyu (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2022)
Introduction: The women with drugs addictive were increasing significantly. As consequence, the recovery was needed to make a better quality of life. In the recovery process they needed social support to prevent relapsing. This study to review how the experience of the women with drugs addiction in their recovery process. Methods: This study used database in early 2011 until 2021, there were BMC, CINAHL, ClinicalKey for Nursing, Embase, Emcare, Emerald Insight, Gale OneFile: Nursing and Allied Health, Informit, Joanna Briggs Institute EBP Database, Medline, Nursing & Allied Health, Proquest, Psycarticles, Psycinfo, Public Health Database, Pubmed, Pubmed Central (PMC), Sciencedirect, Scopus, and Wiley Online Library. The inclusion articles were qualitative original research dan research subject is relevant with the interest of this study. This study will use meta-aggregation for the analysis method. Result: Discussion of result will be made Conclusion: Conclusion and recommendations will be made